Weighing in on the role of brown adipose tissue for treatment of obesity - Brinda Prapaharan; Micah Lea; Jacqueline L. Beaudry (Frontiers Media S.A., 2024)
Brown adipose tissue (BAT) activation is an emerging target for obesity treatments due to its thermogenic properties stemming from its ability to shuttle energy through uncoupling protein 1 (Ucp1). Recent rodent studies show how BAT and white adipose tissue (WAT) activity can be modulated to increase the expression of thermogenic proteins. Consequently, these alterations enable organisms to endure cold-temperatures and elevate energy expenditure, thereby promoting weight loss. In humans, BAT is less abundant in obese subjects and impacts of thermogenesis are less pronounced, bringing into question whether energy expending properties of BAT seen in rodents can be translated to human models. Our review will discuss pharmacological, hormonal, bioactive, sex-specific and environmental activators and inhibitors of BAT to determine the potential for BAT to act as a therapeutic strategy. We aim to address the feasibility of utilizing BAT modulators for weight reduction in obese individuals, as recent studies suggest that BAT's contributions to energy expenditure along with Ucp1-dependent and -independent pathways may or may not rectify energy imbalance characteristic of obesity.